Pengaruh Komunikasi Interpersonal dan Kesejahteraan Terhadap Keharmonisan Keluarga Dharmika di Kota Mataram - Nidiana, I Ketut; Wirawan, I Wayan Ardhi; Yudhiarsana, I Made Agus (Widya Sandhi, 2024)
This study aims to determine the effect of interpersonal communication and welfare on the harmony of the Dharmika family in the city of Mataram. The type of research used is causal associative with a quantitative approach. The population in this study were all Dharmika in the city of Mataram as many as 171 people with a total sample of 120 people. Data collection techniques using a questionnaire. The test results show that: 1) The average value of interpersonal communication is 3.82, 2) The average value of welfare is 3.99, 3) The average value of Dharmika family harmony is 3.75, 4) Interpersonal communication has a positive effect and significant to the harmony of the Dharmika family in Mataram City. The test results obtained tcount > ttable (3.417 > 1.980) with a significance value (0.001 < 0.05), 6) Welfare has a positive and significant effect on the harmony of the Dharmika family in Mataram City. The test results obtained tcount > ttable (3.224 > 1.980) with a significance value (0.002 <0.05), and 6) Interpersonal communication and well-being together have a positive and significant effect on the harmony of the Dharmika family in Mataram City. The test results obtained Fcount > Ftable (15.590 > 3.07) with a significance value (0.000 <0.05). Based on this, it can be concluded that there is an influence of interpersonal communication and well-being on the harmony of the Dharmika family in Mataram City, either partially or simultaneously.